Mengoptimalkan Header Keamanan pada Website Server OpenLiteSpeed ​​Menggunakan Hardening Berbasis OWASP - Sugiyatno Sugiyatno; Untung Subagyo (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2026)
Web service security is essential for maintaining the confidentiality, integrity, and availability of data in modern digital environments. Improperly configured web servers are vulnerable to various security threats, including injection attacks, Cross-Site Scripting (XSS), and brute-force attacks. OpenLiteSpeed is widely adopted due to its high performance; however, its default configuration may still expose security vulnerabilities. This study aims to enhance the security of OpenLiteSpeed web services running on Ubuntu Server through the implementation of OWASP-based hardening techniques, with a particular focus on security header optimization. The novelty of this research lies in the implementation of customized security header configurations, including Content Security Policy (CSP), X-Frame-Options, and HTTP Strict Transport Security (HSTS), tailored to application requirements. An experimental approach was employed, involving vulnerability assessment, firewall configuration, SSL/TLS implementation, permission management, security header optimization, and comparative security testing using OWASP ZAP before and after hardening. The results demonstrate a significant reduction in both the number and severity of vulnerabilities, confirming the effectiveness of OWASP-based hardening in strengthening Linux-based web server security.